Interferon-gamma release assay conversion after Mycobacterium tuberculosis exposure specifically associates with greater risk of progression to tuberculosis: A prospective cohort study in Leicester, UK - Jee Whang Kim; Joshua Nazareth; Joanne Lee; Hemu Patel; Gerrit Woltmann; Raman Verma; Anne O'Garra; Pranabashis Haldar (International Journal of Infectious Diseases, 2024)
Objectives: We investigated whether quantifying the serial QuantiFERON-TB Gold (QFT) response improves tuberculosis (TB) risk stratification in pulmonary TB (PTB) contacts. Methods: A total of 297 untreated adult household PTB contacts, QFT tested at baseline and 3 months after index notification, were prospectively observed (median 1460 days). Normal variance of serial QFT responses was established in 46 extrapulmonary TB contacts. This informed categorisation of the response in QFT-positive PTB contacts as converters, persistently QFT-positive with significant increase (PPincrease), and without significant increase (PPno-increase). Results: In total, eight co-prevalent TB (disease ≤3 months after index notification) and 12 incident TB (>3 months after index notification) cases were diagnosed. Genetic linkage to the index strain was confirmed in all culture-positive progressors. The cumulative 2-year incident TB risk in QFT-positive contacts was 8.4% (95% confidence interval, 3.0-13.6%); stratifying by serial QFT response, significantly higher risk was observed in QFT converters (28%), compared with PPno-increase (4.8%) and PPincrease (3.7%). Converters were characterised by exposure to index cases with a shorter interval from symptom onset to diagnosis (median reduction 50.0 days, P = 0.013). Conclusions: QFT conversion, rather than quantitative changes of a persistently positive serial QFT response, is associated with greater TB risk and exposure to rapidly progressive TB.